Phytochemical screening, antimicrobial and anti-inflammatory activity of crude seeds extract from Pithecellobium dulce (roxb.) Benth - K. UMA SHANKARI,; PREM KUMAR A, (International Journal of Pharma and Bio Sciences, 2019)
Pharmaceutical industry has for long been focused on synthetic drugs but of late, the interest in phytochemistry and phytotherapy has increased. Pithecellobium dulce is a species of flowering plant from the family Fabaceae native to the highlands of Mexico, the Pacific coast, Central America and South America. The plant is well known for its fruit that is consumed raw. Various parts of the plant have been used by traditional medicine practitioners to treat many ailments. The leaves have been used to treat leprosy, ulcer, toothaches and as an abortifacient in folk medicine. In this study, we screened for the presence of some phytochemicals in the seeds of the plant and we also tried to evaluate its anti-bacterial and anti-inflammatory efficacy. The antibacterial properties were studied by zone of inhibition method and the anti-inflammatory efficacy was analysed by Sheep red blood cells (SRBC) membrane stabilization method. The methanolic extract of Pithecellobium dulce seeds was found to be highly potent against the Gram negative bacteria Escherichia coli and Pseudomonas aeruginosa at both the concentrations – 200mg/ml and 300mg/ml. The methanolic extract also showed the highest protection percentage in the RBC membrane stabilization assay. The petroleum ether extract showed a very low protection percentage in the SRBC membrane stabilization method. It also failed to show any anti-bacterial capabilities against the four microbes tested. The study shows that the seeds of Pithecellobium dulce, especially the methanolic extracts possess good anti-bacterial and anti-inflammatory qualities that could be exploited to produce pharmaceutical drugs and nutraceutical formulations. These drugs could be devoid of any side effects which are a major drawback of synthetically manufactured drugs.